Analisis Pembelajaran Berbasis Digital pada Mahasiswa Universitas Muria Kudus - Suryanto, Halim; Setiyawati, Heny Septyan; Yulia putri, Rizqi Dian; Fajrie, Nur (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 24 No 2 (2024), 2024)
Technology-based learning plays an important role in supporting the implementation of learning, with the existence of technology it can help human work as well as a source of information and knowledge. The purpose of this study was to determine the role of digital technology as a support for learning in Muria Kudus University students. In this study using a qualitative descriptive method with a phenomenological approach. This study used a sample of students at Muria Kudus University. The informants of this study were 4 students who were actively pursuing their education at Muria Kudus University. The results of interviews and observations that have been collected are then analyzed. The results of this study indicate that digital technology really helps students in learning at Muria Kudus University.